Step-by-step explanation:
∫ dt / (cos²(t) ⁹√(1 + tan(t)))
If u = 1 + tan(t), then du = sec²(t) dt.
∫ du / ⁹√u
∫ u^(-1/9) du
9/8 u^(8/9) + C
9/8 (1 + tan(t))^(8/9) + C
4 + 8 ln(x) = 2
8 ln(x) =
by exponentiating both sides.
x =
28+3(5d-3)
Answer:
15d+19
Step-by-step explanation:
distribute 3(5d-3) first
= 15d-9
the expression is now 28+15d-9
combine 28 and -9
=19
bam u now have 15d+19
When y = -6 and z = 5, the value of the expression y + z + 2 is 1.
To calculate the expression y + z + 2 when y = -6 and z = 5, you simply substitute these values into the expression and perform the arithmetic operations:
y + z + 2 = (-6) + (5) + 2
Now, perform the addition:
(-6) + (5) + 2 = -1 + 2 = 1
So, when y = -6 and z = 5, the value of the expression y + z + 2 is 1.
for such more question on expression
#SPJ2
Answer:
1
Step-by-step explanation:
y + z + 2
first you have to replace the variables with the numbers
This is your equation now.
-6 + 5 + 2
Now you just have to solve it.
-6 + 5 = -1+ 2 = 1
or
7 - 6 = 1
Step-by-step explanation:
We know that this particularly line can be named as :
This give us the following information :
One statement we can make is :
The points J , K , L and M are aligned. So the line passes through the points J , K , L and M.
We also know that given a line there are infinite planes that contain the line.
Given that the points J , K , L and M belong to the same line, we can state that :
There are infinite planes that contain the points J , K , L and M.